National screening guidelines and developments in prenatal diagnoses and live births of Down syndrome in 1973–2016 in Denmark. (22nd January 2018) - Lou, Stina; Petersen, Olav B.; Jørgensen, Finn S.; Lund, Ida C.B.; Kjærgaard, Susanne; ,; Vogel, Ida
Abstract: Introduction: Denmark was the first country in the world to implement a national, free‐for‐all offer of prenatal screening for Down syndrome to all pregnant women. It has a high uptake (>90%) compared to other countries. Thus, Denmark offers an interesting case for investigating the consequences of implementing comprehensive, national prenatal screening guidelines. The aim of this study was to describe the historical developments in invasive procedures, pre‐/postnatal diagnoses of Down syndrome and Down syndrome live births in the period 1973–2016 in Denmark. Material and methods: Data on invasive procedures, pre‐ and postnatal Down syndrome diagnoses were retrieved from the Danish Cytogenetic Central Registry. Results: From 1973 to 1993, screening based on maternal age and high‐risk indications resulted in a constant increase in invasive procedures. After the introduction of the triple test in 1994, invasive procedures decreased for the first time in 20 years. Following the introduction of an offer of combined screening to all pregnant women in 2004, the number of invasive procedures decreased markedly, while there was a concurrent increase in prenatal diagnoses of Down syndrome. Additionally, the number of Down syndrome live births decreased suddenly and significantly, but subsequently stabilized at 23–35 annual live births. Of these, the majority were diagnosed postnatally. Conclusion: Though prenatal screening technologies constantly improve, it was the introduction of and adherence to national guidelines that resulted in marked shifts in screening procedures and outcome in Denmark.